Gender differences in English learning motivation among the first-year students of Universiti Sultan Zainal Abidin - Azilah Mahammed
Studies have shown that motivation influences the learning of English as a second language. Motivation has been found to not only increases students' drive in language learning but also influences their language performance. Most of the first-year students in Universiti Sultan Zainal Abidin (UniSZA) have been found to have low English performance. This study therefore tries to a) determine the significant difference in the levels of motivation in learning English in terms of gender, b) determine the significant difference in the levels of English performance in terms of gender, c) examine the relationship between motivation and English performance among first-year students of UniSZA, d) explore the factors that influence motivation in learning English among first-year students of UniSZA. The sample for this study comprises 112 first-year students of UniSZA. The data were gathered through the adapted version of Attitude/Motivation Test Battery (AMTB) and also through in-depth interview. The findings revealed that most of the students had high level of motivation and the difference between males and females in terms of their motivation level was significant. Interestingly, females were found to be more motivated than the males. The tudy also discovered that most of the students had moderate level of English performance and there was no significant difference found between the gender. However, a significant relationship was found between motivation and English performance. Four factors which influenced the students' motivation in learning English were also identified. They are academic, employability, social interaction, and entertainment purposes. In conclusion, gender helps in determining student's motivation level but might not be the predictors for their English performance level. Motivation might contribute to students' English performance but other factors might also play a vital role in influencing the performance. Teachers can take into consideration the motivational factors found in this study to enhance their students' performance in learning English.